MENGAWAL KOMITMEN MUTU DOSEN PERGURUAN TINGGI - Asih Setiawati (Jurnal Good Governance, 2018)
Post-training evaluation has received attention, but for basic training (latsar) for CPNS lecturers are still rare, especially those that focus on evaluating the quality commitment of lecturers and escorting after returning to campus. The study uses the case study method, it aims to find out the form of quality commitment along with the escort, maintenance and improvement of post-CPNS public university lecturers.Data were collected from nine subject groups. Each group consisted of one returned lecturer, one colleague, one mentor, and several students. The focus of each group is on the assessment of the commitment to quality, maintenance, and improvement of the returned lecturer, as well as the form of supervision carried out by the mentor. The research findings show that returned lecturers have not been fully sustainable in realizing the commitment to quality for aspects of teaching, research and community service. Meanwhile, related to maintenance and improvement of quality, it is known that there are efforts from lecturers on the basis of their own initiative to maintain and improve quality. Meanwhile, the supervision carried out by universities is still lacking. This research contributes to the knowledge and development of basic training by providing what aspects still have to be added to the program to improve the commitment to quality and supervision of the lecturer after the training.Keywords: basic training, post training evaluation, commitment to quality, lecturer.